Determination of Traveler Permission in Precaution Covid-19 Area Based on Precaution Covid-19 Pandemic (PCP) Level - Yeffry Handoko Putra; Lia Warlina; Selfa Septiani Aulia; Wantoro Wantoro; Dina Fatimah (Universitas Raharja, 2023)
Indonesia from 2020 to 2021 were exposed to COVID-19 pandemic. Both countries implemented a policy of restricting entry areas based on almost the same criteria, In Indonesia namely as PPKM which applying some level of exposure to those infected with covid-19. The determination of this level was all based on the growth in numbers exposed to covid-19, but on pandemic cases, the number of people who do not suffer from COVID-19 disease but have the same symptoms as the symptoms of COVID-19 also need to be considered as the pandemic agent to their environment. We named it as Precaution Covid-19 Pandemic (PCP) Level. The current level of the COVID-19 pandemic has not been fully determined by this idea. So, the idea of this research is to determine the pre-pandemic or precaution level of covid-19 in an area interfere by surrounding area. PCP level was not based on the growth of those infected with the covid-19 disease, but influenced by the number of patients whose have the symptoms similar to the dominant symptoms of the covid-19. The PCP Level determination can be used for precaution policy and support the previous Level Pandemic Methods. To accomplish this idea, two algorithms are used, they are K-Mean algorithm as a pattern clustering and the AHP algorithm as a level determination of the Covid-19 pandemic. Data are collected from 11 health centers in Bandung Regency. The last thing is two determine the allowance for travel to other town is done by check the tendency for traveler to be infected determine by the PCP Level and using Naïve bayes algorithm which recognizing the pattern of symptoms. The results of this study show that the combination of the three proposed algorithms can be used as alternative to give warrant decision about getting infection of Covid-19